Structure and quantitative phytoplankton development of watercourses of the National Park «Pripyatsky» - Mikheeva, Tamara M.; Svirid, Anna A.; Lukyanova, Elena V. (Experimental Biology and Biotechnology, 2017)
The data on taxonomic structure, on the level of summer phytoplankton biomass and the degree of phytoplankton community colonization and average mass of plankton unity in Pripyat’ River and its tributaries (right-bank – Stviga, Svinovod, Snyadinka, Belyanka, Ubort’ and left-bank – Skripitsa, Naut’, Utvokha), in streams and channelized streams (right-bank – Krushinny, Bytchok, Khlupinsky – relief channel drainage system and left-bank – Najdo-Belevsky, channel-gatherers pond system beside pumping station near r. Naut’, Lutchinez stream and others) located within National Park «Pripyatsky» (Belarus) are represented. 218 phytoplankton species were revealed in rivers and 102 in streams and channelized streams, the mostly diverse were green algae. Differences’ range of total phytoplankton biomass in rivers was 0.05–9.01 mg/l. In streams and channelized streams it was more wider – from 0.1 to 48.8 mg/l. The more high degree of colonization and its variability was inherent to phytoplankton organisms of r. Pripyat’: minimal cell number per organism was equal to 6.8, maximal – to 93.0. The organisms with the lowest weight (0,042 ∙ 10–6 mg) inhabited Krushinny channel. The high specificity of investigated watercourses was inherent to all of them.